IJMA’ DALAM USHUL FIKIH (SYARIAH: Journal of Islamic Law, 2022)
In Islamic legal theory (uṣul al-fiqh), ijmam is the third source of law after the Koran and sunnah (hadith). During the early legal schools of thought, the position of ijmaid was fourth. There was a shift in position after entering the Imam ash-Shafi'i period, and it was strengthened again in the classical period, the function and position of ijmaa became static, rigid, formal, final, not prospective for the future, and did not allow ijmaat to occur in the future. come. The concept of ijmaat during the early legal schools of law was a principle of justification to state the legitimacy of various different opinions, as an effort to find common ground and agree in establishing syar'i law. Al-Qur'an and sunnah are the propositions that create, while qiyas, ijmaak, and others are the propositions that reveal in finding the law. The concept of Ijmak was originally something dynamic and there was a harmonious integrative relationship between sunnah, ijtihad and ijmaak, but after the ash-Shafi'i period, ijmaq changed and shifted to be static, formal, not prospective for the future, the object of study is very limited, and Ijma is only possible during the friendship period, in the future it is not possible. It was even worse in the classical period, ijmaq became something that was final, and could not be changed until "the door to ijtihad was closed", conformity developed and madhhab fanatics. The model of consensus that is needed in this modern era is democratic consensus organized in the form of legislative institutions at the national and international levels. These institutions are needed to accommodate various interests and agreements in every nation-state, and the international community to discuss crucial international issues, such as humanitarian, human rights, justice, economic, and terrorism problems regardless of ethnic, racial, religious and cultural backgrounds, the important thing is that we all have a commitment to improving human life in the international world. And the results of formal and non-formal consensus can in time be changed again in line with developments in the situation and conditions of modern times.